2012
DOI: 10.1097/pat.0b013e3283513f3b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathways involved in crosstalk between cancer cells, osteoblasts and osteoclasts in the invasion of bone by oral squamous cell carcinoma

Abstract: We regret that in Volume 44, Supplement 1, an abstract by Hutchison et al. was omitted from page S12 in the section 'Anatomical, Oral and Maxillofacial Pathology including workshops'.1 It is published in full below:TENNIS RACQUETS IN THE JAW: EOSINOPHILIC GRANULOMA A healthy 4-year-old boy presented with a 4 month history of episodic pain and swelling of his left jaw which appeared to respond to antibiotics. An ultrasound, orthopantomogram (OPG), CT scan and MRI revealed a 3 cm well circumscribed lesion in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
0
19
0
3
Order By: Relevance
“…Human foetal osteoblasts (hFOB) were obtained from American Type Tissue Collection (ATCC, Rockville, USA), and grown in DMEM/F12 with 10 % FBS plus 300 μg/mL geneticin (G418) at 34 °C in an incubator. CM [17] was collected from OSCC cell lines SCC15 and SCC25, and from hFOB, and used for indirect co-culture: OSCC cells were treated with CM of hFOB cells for 48hs. To block the endogenous TGF-β1 secreted by hFOB cells, TGF-β inhibitor (SB431542, 188 nM, Sigma) was used in CM of hFOB to treat OSCC cells for 48 h. To examine the effects of TGF-β1 on OSCC cells, equal numbers of SCC25, HN5 and Tca8113 cells were plated in serum-free medium, starved for 12 h, and then treated with TGF-β1 (5 ng/mL) for 0, 1–3 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human foetal osteoblasts (hFOB) were obtained from American Type Tissue Collection (ATCC, Rockville, USA), and grown in DMEM/F12 with 10 % FBS plus 300 μg/mL geneticin (G418) at 34 °C in an incubator. CM [17] was collected from OSCC cell lines SCC15 and SCC25, and from hFOB, and used for indirect co-culture: OSCC cells were treated with CM of hFOB cells for 48hs. To block the endogenous TGF-β1 secreted by hFOB cells, TGF-β inhibitor (SB431542, 188 nM, Sigma) was used in CM of hFOB to treat OSCC cells for 48 h. To examine the effects of TGF-β1 on OSCC cells, equal numbers of SCC25, HN5 and Tca8113 cells were plated in serum-free medium, starved for 12 h, and then treated with TGF-β1 (5 ng/mL) for 0, 1–3 days.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we found that conditioned medium (CM) of osteoblasts induced gene expression level changes of OSCC cells [17], for example, Twist1, was up-regulated in these cells after such treatment. The expression of MMP-2 protein level was increased, while MMP-9 was decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was demonstrated that the functions of OB and OC showed correlative dependence (Choi et al, 2012;Yamashita et al, 2012). OB could regulate OC maturation and activation by secreting interleukin and other cytokines (Quan et al, 2012). However, the mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Inicialmente, as células tumorais secretam proteases, que são enzimas capazes de degradar componentes da matriz extracelular, facilitando a invasão do tumor pelos tecidos. As proteases também atuam na diferenciação das células ósseas, recrutando osteoclastos que passam a reabsorver a matriz mineralizada do osso (26,27…”
Section: Mecanismos Moleculares Da Invasão óSseaunclassified
“…As MMPs são uma parte essencial do equilíbrio do processo de formação/reabsorção óssea em condições normais, mas também são expressas pelas células tumorais (33). No câncer, as MMPs contribuem para a migração celular e também tem uma participação essencial na diferenciação e maturação das células ósseas (26,27).…”
Section: Mmpsunclassified